INCREASING LEVEL OF EYE HEALTH WITHHEALTH EDUCATION COLOR BLINDNESS SCREENING METHODIN THE BULAKDAWUNG STUDY GROUP KEDIRI - Sandy Kurniajati; Yoyok Febrijanto; Sutik; Corlida Priska K.D; Helen Pakpahan; Oky Wahyu S. (Pedagogic Research-Applied Literacy Journal, 2024)
Implementation of increasing level of eye health using health education using color blind screening method in the Bulakdawung Study Group Kediri showed that increasing in the knowledge of parents and children regarding eye health through health education using color blind screening method with 100% results of not experiencing color blindness. Parents need to maintain eye health by providing nutrition/diet to children with a source of vitamin A, need to prevent eye trauma when children play, and to give health education to prevent eye trauma in children. In play groups, it is necessary to provide supplementary food rich sources of Vitamin A periodically every 2-3 months and eye health education to children in study groups.